2020
DOI: 10.1186/s12877-020-01683-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of frailty on admission to home care services and nursing homes: eight-year follow-up of a community-dwelling, older adult, Spanish cohort

Abstract: Background: Frailty in older adults is a common multidimensional clinical entity, a state of vulnerability to stressors that increases the risk of adverse outcomes such as functional decline, institutionalization or death. The aim of this study is to identify the factors that anticipate the future inclusion of community-dwelling individuals aged ≥70 years in home care programmes (HC) and nursing homes (NH), and to develop the corresponding prediction models. Methods: A prospective cohort study was conducted in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 57 publications
6
38
0
Order By: Relevance
“…The incidence of NHA may be in uenced by organizational aspects and the cultural aspects [47], but also by the availability, accessibility and affordability of home care facilities. The characteristics of the study population also play a role since the cumulative incidence of NHA could be affected by the higher risk of death in the population under study.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of NHA may be in uenced by organizational aspects and the cultural aspects [47], but also by the availability, accessibility and affordability of home care facilities. The characteristics of the study population also play a role since the cumulative incidence of NHA could be affected by the higher risk of death in the population under study.…”
Section: Discussionmentioning
confidence: 99%
“…The 5×STS is an important component of the Short Physical Performance Battery, a clinical tool used for identifying physical frailty [ 32 ]. Therefore, sensor-based 5×STS could enable health professionals to quickly identify slowness, weakness, and exhaustion, which can assist in recognizing potential modifiable risk factors to improve health outcomes and strategies for older adults [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…36e40 Moreover, low educational level is frequently noted in people admitted to nursing homes. 41,42 Of note, a recent pilot study reported that frail institutionalized older adults showed reduced episodic memory after a unique session of HSRT. 43 When these data are interpreted in light of our case study, they suggest that HSRT might be a cognitively demanding task to frail nursing home residents, specifically for those untrained.…”
Section: Have Frail Institutionalized Older Adults Sufficient Cognitive Resiliency To Perform Hsrt?mentioning
confidence: 99%